Getting out of a problem - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau should be proud of its protective handling of the Covid-19 pandemic, as it has managed to contain its spread, and many of its citizens have been able to lead a more normal life than in other parts of the world. We should be grateful for this.